STRATEGI PESANTREN DALAM MENUMBUHKAN ENTREPRENEURSHIP SANTRI - Humaidi, Rif’an; Auniyah, Jazilatul (Balai Besar Guru Penggerak Jawa Timur, 2023)
The purpose of this research is to describe: 1) the of the Islamic boarding school's strategy in the planning stage in fostering santri entrepreneurship. 2) of the Islamic Boarding School strategy in the implementation stage in fostering santri entrepreneurship. 3) of the Islamic Boarding School strategy in the evaluation stage in fostering santri entrepreneurship. This research uses a qualitative approach with a descriptive type. Data analysis techniques used Miles, Huberman namely: data condensation, data presentation, and data verification/conclusion. The validity of the data uses source triangulation and technical triangulation. The results of this research are the Islamic Boarding School's strategic in fostering student entrepreneurship at the Raden Rahmad Sunan Ampel Antirogo Jember Islamic Boarding School which includes the planning, implementation and evaluation stages. The planning stage includes the following steps: formulation of the vision, environmental assessment, organizational assessment and determination of the santri strategy. While the implementation phase includes strategy implementation, change analysis, change planning, communicating changes and consolidating changes. The evaluation phase includes review activities and performance measurement.AbstrakTujuan penelitian ini adalah untuk mendeskripsikan: 1) strategi Pesantren pada tahap perencanaan dalam menumbuhkan entrepreneurship santri. 2) strategi Pesantren pada tahap implementasi dalam menumbuhkan entrepreneurship santri. 3) strategi Pesantren pada tahap evaluasi dalam menumbuhkan entrepreneurship santri. Penelitian ini menggunakan pendekatan kualitatif dengan jenis deskriptif. Teknik analisis data menggunakan Miles, Huberman yaitu: kondensasi data, penyajian data, dan verifikasi/ kesimpulan data. Keabsahan data menggunakann trianggulasi sumber dan trianggulasi teknik. Hasil dari penelitian ini strategi Pesantren dalam menumbuhkan entrepreneurship santri di Pondok Pesantren Raden Rahmad Sunan Ampel Antirogo Jember mencakup tahap perencanaan, implementasi dan Evaluasi. Tahap perencanaan meliputi langkah-langkah: perumusan visi, asesmen lingkungan, asesmen organisasi dan penentuan strategi santri. Sedangkan tahap implementasi meliputi implementasi strategi, analisa perubahan, perencanaan perubahan, mengkomunikasikan perubahan serta mengkonsolidasi perubahan. Tahap evaluasi meliputi aktivitas peninjauan ulang dan pengukuran kinerja.